Use of whey peptide fraction in coated cashew nut as functional ingredient and salt replacer - Amorim, M.; Pereira, J.O.; Silva, L.B.; Ormenese, R.C.S.C.; Pacheco, M.T.B.; Pintado, M. (Food science & technology, 2018)
Consumers are increasingly concerned about healthy eating habits. The incorporation and stability of 2% antihypertensive whey peptide extract in a new coating of cashew nuts with reduced salt (less 15 and 30%) was studied. The evaluation of nutritional value, in vitro antihypertensive activity and consumer acceptance of final products was assessed. Incorporation of peptide fraction assured the production of a snack with an ACE-inhibitory activity (532.2 μg mL−1 IC50 value). The amount of lipids present in coated cashew nuts was composed mainly by essential fatty acids, mostly monounsaturated. Glutamic acid, leucine, arginine and aspartic acid were the most abundant essential aminoacids. 70% of the consumers considered both samples (15 and 30%) as “ideal taste”. The results suggest that the new coating allowed the development of a new snack with reduced salt content, opening new opportunities as carrier of other ingredients to develop more diversified and efficient functional foods. •Development of a new functional coated cashew nut with whey peptide fraction.•Coated cashew nut with relevant antihypertensive peptides.•Snack with reduced salt, healthy lipids and amino acid profile.•Coated cashew nut had a very good acceptance and high purchase intention by consumers.